2006
DOI: 10.2325/jbcs.13.272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of matrix metalloproteinase-2 (mmp-2) activity with film in situ zymography for improved cytological diagnosis of Breast tumors

Abstract: The present study demonstrated that measurement of gelatinolytic activity by FIZ analysis of aspiration cytology samples may be useful for improving the cytological diagnosis of breast tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…In particular, we showed that silencing MMP2 expression all but eliminated gelatinase activity in AF cells and profoundly compromised their ability to remodel collagen matrices. We also demonstrated that, similar to tumor invadopodia [20-23], MMP-2 preferentially functions in a localized region surrounding AF cells, rather than being secreted and acting at a distance. Contrary to our expectations, the impaired ability of AF cells to degrade and remodel their local microstructure did not translate to the macroscale characterization of the collagen-gel mechanical properties.…”
Section: Discussionsupporting
confidence: 52%
“…In particular, we showed that silencing MMP2 expression all but eliminated gelatinase activity in AF cells and profoundly compromised their ability to remodel collagen matrices. We also demonstrated that, similar to tumor invadopodia [20-23], MMP-2 preferentially functions in a localized region surrounding AF cells, rather than being secreted and acting at a distance. Contrary to our expectations, the impaired ability of AF cells to degrade and remodel their local microstructure did not translate to the macroscale characterization of the collagen-gel mechanical properties.…”
Section: Discussionsupporting
confidence: 52%
“…To detect the localization of gelatinolytic MMP activity in skeletal muscle tissues, we performed film in situ zymography (FIZ) as previously described [42-48]. 6 μm-thick cryosections from frozen samples were placed on a polyethylene terephthalate base film coated with 7 μm thickness cross-linked gelatin with (FIZ-GI, Wako Pure Chemical, Osaka, Japan) or without (FIZ-GN, Wako Pure Chemical) 1,10-phenanthroline (inhibitor of MMPs, but not of other proteinases such as trypsin).…”
Section: Methodsmentioning
confidence: 99%
“…The human fibrosarcoma cell line HT1080 is known to secrete relatively high amounts of proMMP-2 [25]. Treatment of the cells with (GPO) 10 almost doubled the invasive capacity of the tumour cells, indicating an enhanced activation of endogenous proMMP-2 by (GPO) 10 in the supernatant.…”
Section: Discussionmentioning
confidence: 99%